LITERATURE REVIEW: PERAN MEDIA SOSIAL DALAM PEMASARAN FILM INDONESIA: ANALISIS KEPUASAN DAN NIAT BELI PENONTON - Muhammad Fadheel Djamaly; Djumarno Djumarno; Rina Astini; Daru Asih (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This literature review article discusses the role of social media in Indonesian film marketing with a focus on analyzing audience satisfaction and purchase intent. This study was conducted to see the extent to which the use of social media can affect audience satisfaction and purchase intention towards Indonesian films. The method used in this study is to conduct a literature study of previous studies related to the role of social media in film marketing. In its analysis, the study found that the use of social media can increase audience satisfaction and also influence their purchase intention towards Indonesian films. Previous studies have shown that the use of social media can provide more complete and faster information about upcoming films, as well as provide a more interactive experience for viewers. With more complete and interactive information, viewers feel more satisfied with the viewing experience, and have a greater tendency to buy tickets for the film. In addition, the study also found that social media use can influence viewers' purchase intent through the influence of movie recommendations and reviews by other social media users. The more people who recommend and give positive reviews about the film on social media, the greater the audience's buying intention to watch it. In conclusion, the study shows that the use of social media plays an important role in the marketing of Indonesian films, and can affect audience satisfaction and purchase intent. Therefore, film producers in Indonesia can utilize social media more effectively in their film marketing campaigns to increase audience satisfaction and purchase intent.